Earnings Management: The Interaction of Tax Planning, Leverage, and Sales Growth (E-Jurnal Akuntansi, 2026)
Earnings management is an important issue in the transparency of public companies' financial reports because it can reduce investor and creditor confidence. This study aims to examine the effect of tax planning, leverage, and sales growth on profit management practices in consumer goods manufacturing companies listed on the Indonesia Stock Exchange for the period 2022–2024. The research method used a quantitative approach with secondary data in the form of financial reports, analysed through panel data regression using the Random Effect model. The results show that tax planning and leverage have a positive and significant effect on earnings management, while sales growth has no effect. These findings confirm that contractual pressure due to debt and aggressive tax planning practices are the main drivers of earnings management, while sales performance is not a determining factor. The conclusion of the study emphasises the importance of monitoring capital structure and implementing Good Corporate Governance to minimise opportunistic behaviour by managers.
Keywords: Earnings Management; Leverage; Sales Growth; Tax Planning